Design and implementation of a dual polarised L-band parabolic dish antenna for NeXtRAD - Paine, Stephen Thomas (Department of Electrical Engineering, 2016)
Research into multi-static, multi-band networked radar has led to the development of the NeXtRAD radar system. This dissertation will investigate the design and implementation of a dual polarised L-Band prime focus dish antenna with a centre frequency of 1.3 GHz and a HPBW of 10° in the azimuth plane. The antenna is required to handle a peak power of 1.5 kW over a 50 MHz bandwidth and be able to withstand environmental factors such as wind while mounted on a tripod. This dissertation forms part of the larger NeXtRAD project and as such, the antenna design requirements have been set based on the wider system specifications. Previous investigations into the feasibility of various antenna designs have concluded that a prime focus parabolic dish antenna would be the most appropriate to meet the design requirements. The dissertation details the design and manufacturing process followed. All antenna parameters have been simulated using a combination of FEKO v7 and CST 2014 to compare and verify the designs and simulations. Due to manufacturing limitations, the optimal antenna design could not be manufactured and, as a result, compromises had to be made in order for an antenna prototype to be manufactured and tested. These tests include, amongst others, characterisation of the return loss, cross polarisation, gain, beamwidth and beam pattern of the antenna in both planes of polarisation. These results have been recorded, analysed and compared to those found through simulations.